Protective layer for tunnels under rock fall impacts - Rezagholilou, Alireza; Nikraz, H. (2013)
Falling objects such as rock segments can be considered as a loading case in design of tunnels. One way to control this issue is to use soil cushion layer as protection measure to lessen the induced pressures on the lining. To evaluate this type of loading case and its effects on the lining, different highly variable factors need to be considered and studied. Therefore, in this paper, effective factors in design of protective fill layer will be evaluated by different experimental and analytical methods. Analytical method is based on simple dynamic analyses by finite element method. © 2013 Taylor & Francis Group.